THE ASSOCIATION BETWEEN MALIGNANT OTITIS EXTERNA AND DIABETES MELLITUS : A SYSTEMATIC REVIEW - Setyo Nugroho, Bayu (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Diabetes mellitus is one of the risk factors for malignant otitis externa. There are very few studies on the disease and there is a need to pool the prior studies to highlight the characteristics of the disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 177 articles, whereas the results of our search on SagePub brought up 56 articles. The results of the search conducted for the last year of 2013 yielded a total 59 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 4 papers, 3 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: MEO is an aggressive type of external otitis leading to osteomyelitis of the skull base bone. The usual microorganism involved is Pseudomonas species, and it usually affects individuals with diabetes mellitus. Treatment of the disease has changed over the years, today following conservative treatment modalities with antibiotics and conducting surgery under special circumstances. MEO is a rare but fatal disease, and the specialists involved in its diagnosis and treatment, namely ENT surgeons and diabetes specialists, should be aware of it.